Comparison of State-owned and Private-owned Emerging Market Enterprises’ Internationalization: Case Studies of State-owned China Mobile’s and Private-owned Huawei’s Cross-border Acquisitions. - Kaneva, Mariya (2014)
This research examines the cross-border activities of emerging market enterprises.By incorporating the mainstream theories of internationalization with institutional theory and analyzing the seemingly contrasting views within institutional theory of institutional escapism and government support in pushing the international expansion of firms from emerging markets, this study allows us to see the different determinants for internationalization of firms with different ownership structure. The research also highlights the different motives of cross-border expansion for state-owned and private-owned firms.